2014
DOI: 10.1016/j.biopsych.2013.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Biomarkers for Early Drug Development in Schizophrenia

Abstract: Given the relative inability of currently available antipsychotic treatments to adequately provide sustained recovery and improve quality of life for patients with schizophrenia, new treatment strategies are urgently needed. One way to improve the therapeutic development process may be an increased use of biomarkers in early clinical trials. Reliable biomarkers that reflect aspects of disease pathophysiology can be used to determine if potential treatment strategies are engaging their desired biological target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 115 publications
(115 reference statements)
2
37
0
Order By: Relevance
“…Neuroimaging has developed into an invaluable tool for drug discovery and development Fox et al, 2009;Hargreaves et al, 2010;McArthur, 2012;Tregellas, 2014;von Kienlin and Risterucci, 2010;Wan et al, 2010;Wong et al, 2008a).…”
Section: Neuroimagingmentioning
confidence: 99%
“…Neuroimaging has developed into an invaluable tool for drug discovery and development Fox et al, 2009;Hargreaves et al, 2010;McArthur, 2012;Tregellas, 2014;von Kienlin and Risterucci, 2010;Wan et al, 2010;Wong et al, 2008a).…”
Section: Neuroimagingmentioning
confidence: 99%
“…For example, intrinsic hippocampal hyperactivity and default network hyperactivity are two promising, potential biomarkers for schizophrenia that have been identified in large part by fMRI [28]. The effectiveness of these biomarkers depends not only upon their ability to be associated with clinical outcomes, but also their ability to predict treatment response.…”
Section: Biomarkers Of Neural Responsesmentioning
confidence: 99%
“…The effectiveness of these biomarkers depends not only upon their ability to be associated with clinical outcomes, but also their ability to predict treatment response. As reviewed by Tregellas [28], both hippocampal hyperactivity and dysfunction within large-scale networks have demonstrated promise in fulfilling these criteria. These results, however, are in need of validation by larger studies, particularly in determining how effects of both established and investigational therapies may target these biomarkers to produce treatment effects.…”
Section: Biomarkers Of Neural Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging studies in human patients frequently have observed increased activity in the hippocampus in patients with schizophrenia, relative to comparison subjects (reviewed by Heckers and Konradi (2014); Tamminga et al (2012); Tamminga et al (2010); Tregellas (2014)). The magnitude of this abnormality may predict positive (Ebmeier et al, 1993; Friston et al, 1992; Gur et al, 1995; Kawasaki et al, 1996; Liddle et al, 1992; Molina et al, 2005; Schobel et al, 2013; Schobel et al, 2009), negative (Schobel et al, 2009; Tregellas et al, 2014), and cognitive (Tregellas et al, 2014) symptoms.…”
Section: Introductionmentioning
confidence: 99%